The Effects of Non-Debt Tax Shields, Company Size, and Asset Structure on the Capital Structure of the Technology Sector - Tari Apriani; Enggar Diah Puspa Arum; Ilham Wahyudi; Wiralestari Wiralestari (Blantika: Multidisciplinary Journal, 2026)
The dynamic nature of the economy and the dominance of intangible assets have made determining an optimal funding structure in the technology industry increasingly complex. This research aims to analyze the effect of non-debt tax shields, firm size, and asset structure on the capital structure of technology sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This research employs a quantitative approach with panel data regression analysis, processed using EViews 13. The sample consisted of 20 companies selected through purposive sampling, yielding 100 firm-year observations. The results of the partial test show that the non-debt tax shield has a negative and significant effect on capital structure, while firm size has a positive and significant effect. In contrast, asset structure has no significant effect. Simultaneously, these three variables collectively affect capital structure, with an adjusted R-squared value of 34.12%. The findings of this study confirm the relevance of trade-off theory in the technology sector in Indonesia, whereby non-debt tax shield capacity and operational scale serve as the primary determinants of financing policy. The implications of these findings suggest that technology companies should prioritize the capitalization of intangible assets to achieve tax efficiency without increasing default risk, while creditors are encouraged to shift their valuation paradigm from tangible collateral toward innovation potential and intangible asset value.